Magnetic hybrid chitin-horse manure humic acid for optimized Cd(II) and Pb(II) adsorption from aquatic environment - Rahmat Basuki; Yusuf Bramastya Apriliyanto; Elva Stiawan; Adya Rizky Pradipta; Bambang Rusdiarso; Budi Riza Putra (Case Studies in Chemical and Environmental Engineering)
Hybrid magnetic-humic acid-chitin (HMHA-Ch-Fe3O4) was successfully prepared from horse manure and crab shell waste as economical and green adsorbent for Cd(II) and Pb(II). The success synthesis of HMHA-Ch-Fe3O4 was confirmed by diverse instrument. The FT-IR study showed that the HMHA-Ch-Fe3O4 had the combination of characteristics peaks of HMHA, chitin, and Fe3O4. Based on Brunauer, Emmett, and Teller's (BET) theory, the HMHA-Ch-Fe3O4 specific surface area (52.26 m2/g) was higher than original HMHA (35.71 m2/g). The average pore size of HMHA-Ch-Fe3O4 (7.33 nm) was within the mesoporous range (2–50 nm). HMHA-Ch-Fe3O4 ferromagnetism was exhibited by the vibrating sample magnetometer (VSM), which determined magnetic saturation (Ms) at 40.70 emu/g. Applicability of HMHA-Ch-Fe3O4 was thoroughly investigated in batch experiments using an aqueous solution. Four isotherm (Langmuir, Freundlich, Temkin, and Dubinin-Radushkevich (DR)) and six kinetic models (Lagergren, Ho, Santosa, Rusdiarso-Basuki-Santosa (RBS), Elovich, and Intraparticle Diffusion) were conducted to investigate the mechanism of Pb(II) and Cd(II) adsorption on HMHA-Ch-Fe3O4. Among the models, DR isotherm model and Ho kinetics models were found to be more suitable than others for Cd(II) and Pb(II) adsorption reactions. With correlation coefficient (R2 = 0.9989 for Cd(II) and R2 = 0.9985 for Pb(II)), the DR model indicates multilayer adsorption of 288.72 mg/g Cd(II) and 782.95 mg/g Pb(II) on HMHA-Ch-Fe3O4 surface. The maximum monolayer adsorption deduced by Langmuir isotherm model of 95.55 mg/g and 127.94 mg/g for Cd(II) and Pb(II), respectively. The kinetic correlation coefficient (R2 = 0.9998 for Cd(II) and R2 = 0.9989 for Pb(II)) of the Ho kinetics model indicates that the Cd(II) and Pb(II) adsorption onto magnetite was dominated by chemisorption. In addition, up to five adsorption-desorption cycles, the Cd(II) and Pb(II) adsorption was 84.29 % and 88.71 %, respectively. By the eluent 0.1 M HNO3, desorption of Cd(II) and Pb(II) from the adsorbent surface was 93.87 % and 90.71 %, respectively, demonstrating enhanced recycling potential and cost-effectiveness. Moreover, the feasibility and cost-effectiveness study broaden their applicability as environment-friendly adsorbents for Cd(II) and Pb(II) uptake from aquatic environment.